Speech in Noise With Bilateral Active Bone Conduction Implant for Conductive and Mixed Hearing Loss. Issue 9 (30th October 2022) - Canale, Andrea; Ndrev, Drita; Sapino, Silvia; Bianchi, Carlotta; Bordino, Valerio; Albera, Andrea
Abstract : Objective: To evaluate speech in noise results and subjective benefit in bilateral active bone conduction implant (ABCI) for bilateral mixed hearing loss. Study Design: Prospective, comparative. Setting: Ear, Nose and Throat Unit, Department of Surgical Sciences, University of Turin. Patients: Seven patients with conductive/mixed hearing loss. Intervention(s): Patients underwent simultaneous or sequential bilateral surgery for ABCI. Main Outcome Measure(s): The speech intelligibility in noise was assessed with the Ita Matrix test in summation, squelch and head shadow settings. First, the tests were performed with one device activated in the ear with lower speech recognition score, then with both devices. Patients filled in an Abbreviated Profile of Hearing Aid Benefit (APHAB) questionnaire to investigate the hearing aid benefit. Results: When bilateral devices were activated, an improvement of signal-to-noise ratio was observed in all settings. The difference between bilateral and unilateral stimulation is 4.66 dB ( p = 0.016) in the summation, 2.24 dB ( p = 0.047) in the squelch, 7.50 dB ( p = 0.016) in the head shadow setting. Looking at the APHAB global score (GS), patients report lower mean scores, hence less difficulties, when using two devices (GS, 21.9%; standard deviation (SD), 8.28) rather than one (GS, 33.0%; SD, 10.24) ( p = 0.018). Conclusion: In symmetric mixed bilateral hearing loss, rehabilitation with an ABCI fitted bilaterally shows audiologic advantages in speech perception in noise, not only thanks to the summation effect and by reducing head shadow but also by improving the binaural unmasking based on the squelch effect. Audiometric outcomes are confirmed by the GSs obtained in the APHAB questionnaire.